THE HUMAN SIDE OF AUDITING. - Reves, William F. (The Accounting Review, 1946)
The human side of the auditor is remembered by the client or the persons affected long after the detail of the audit is forgotten. One may not be the best auditor in the world, but he can try to be the most helpful. And, if he makes a sincere effort in this direction, his friendliness and his helpfulness will endear him to the persons involved regardless of the nature of the report he renders. When the author became an auditor, it became his duty to render a report which in effect severely criticized the head of a department because of deficiencies and irregularities existing within his organization. Almost immediately after the report had been submitted, a separate situation arose within his own department in which it was imperative that the help and favor of that same department head be secured. To a friend who knew the course of both events, the author could not refrain from voicing his belief that the two jobs were in utter conflict and that eventually he would be compelled to sacrifice one duty so as to fulfill the other. The case did not work out as he expected, however.